Analysis of potential target genes to deliver plant abiotic stress tolerance - Littler, Jasmine (2025)
With ongoing climate change, the need for crops to grow with yield stability in a range of stressful environments is increasingly challenging. Improvement needs to be made to the abiotic stress tolerance of crop plants in order to meet the food demands of an increasing population. Heat has particularly negative effects on reduced photosynthetic efficiency, enzyme activity, and changes in metabolic processes, while drought and waterlogging stress cause stomatal closure, reduced photosynthesis, disrupted nutrient uptake, and cellular damage, ultimately hindering growth and development. One method of increasing plants tolerance to abiotic stress is through targeted mutagenesis. In this study, several genes were selected from a previously published Genome Wide Association Study (GWAS) (Robson et al., 2023) as candidate genes linked to photosynthetic heat stress tolerance in Rice. In A. thaliana, T-DNA insertion mutations in putative orthologue genes to those selected in rice were grown under normal conditions and high temperature stress (22°C and 32°C). Chlorophyll fluorescence was used to characterise mutant lines for photosynthetic heat stress tolerance, fertility, and root architecture. T-DNA insertion lines carrying mutations in ATP BINDING CASSETTE F 5(ABCF5), ZINC NUTRIENT ESSENTIAL1 (ZNE1), and the relatively uncharacterised gene, T8P21, all showed positive photosynthetic traits after five days of heat stress, while mutants in CALLOSE SYNTHASE 1 (CALS1), SYNAPTOTAGMIN 2 (SYTB) and ALBINO OR PALE GREEN 3 (APG3) showed increased sensitivity to heat stress. Alongside the identification of genes associated with photosynthetic heat stress tolerance, Targeting Induced Local Lesions in Genomes (TILLING) mutations in Hordeum vulgare in pathways associated with abiotic stress tolerance in the field were explored. TILLING lines in two components of the Arg/N-degron pathway, which is a conserved pathway associated with abiotic stress tolerance were assessed. TILLING mutations targeting genes in this pathway: PROTEOLYSIS 6 (PRT6) and Gln-specific N-terminal amidase (NTAQ), were tested in the field. Alongside these TILLING mutants, ABSCISIC ACID INSENSITIVE 5(ABI5) mutants were also tested in the field in Hordeum vulgare. Overall, this study has conducted an analysis to identify candidate genes for targeted mutagenesis to overcome abiotic stress in crops at different points in crop development, including both identifying target genes, and testing on the field.